A espiritualidade de mulheres com câncer de mama: um estudo na ótica da teoria do cuidado transpessoal - Birk, Noeli Maria (2016)
Falling ill with cancer is a human experience that, by their socio-cultural meanings and stigmas, refers to facing existential questions and the search for resources to help make sense of what is being lived. The attention focused on the spiritual dimension becomes increasingly necessary to practice in health care, as science gradually recognizes the fundamental role of spirituality in the dimension of the human being. The study's research question: what is the perception of women diagnosed with breast cancer in relation to spirituality as a coping strategy of the disease? The overall goal is to understand the perception of women diagnosed with breast cancer in relation to spirituality as the disease coping strategy, and specific objectives are to know the meanings that women with breast cancer attaches to spirituality; identify strategies related to spirituality used in fighting the disease / treatment; know how women diagnosed with breast cancer perceive the care provided by nurses in relation to spirituality. This is a descriptive research with a qualitative approach, guided by the theoretical framework of the Theory of Human Caring, in an department of oncology of a teaching hospital in the central region of the state of Rio Grande do Sul. Data were collected from March to June 2015, through semi-structured interviews with 14 women who underwent cancer treatment, after approval of the Research Ethics Committee, Nº 991.305. Data analysis was performed according to the content analysis technique. Resulting in the development of four categories, that approach the extent of women with breast cancer and their meanings, the driving force to face the adversities of illness, spirituality and self-esteem, nursing and spiritual care. Therefore, it was understood that spirituality was an effective coping strategy in the face of illness from breast cancer. The results of this study may provoke reflections that allow rethink the practices developed by nurses not only about the spirituality of people they interact, but also bes ides contribute to strengthening the practice in the care of the spiritual dimension.